1996
DOI: 10.1897/1551-5028(1996)015<0937:faeoth>2.3.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Fate and Effects of the Herbicide Atrazine in Flow-Through Wetland Mesocosms

Abstract: Abstract-Wetland mesocosms were exposed to increasing concentrations of atrazine over time at levels typical of midwestern surface waters following spring runoff (15 to 75 g/L). Atrazine had a half-life of 8 to 14 d in the 230-m-long wetlands. End points measured included nutrient levels; periphyton biomass; periphyton productivity and respiration; growth of selected macrophytes; and survival and growth of Daphnia magna (15, 25 g/L atrazine), Rana pipiens (15, 25 g/L), and Pimephales promelas larvae (25 to 75 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0
1

Year Published

2000
2000
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 0 publications
2
25
0
1
Order By: Relevance
“…They also support the notion that the indirect effects of atrazine agricultural applications via surface runoff to adjacent streams and leaching to groundwater reservoirs constitute a serious risk for aquatic systems (Detenbeck et al 1996;Graymore et al 2001).…”
Section: Efficacy Of the Bioremediation Tool In Soil Retention Functisupporting
confidence: 73%
“…They also support the notion that the indirect effects of atrazine agricultural applications via surface runoff to adjacent streams and leaching to groundwater reservoirs constitute a serious risk for aquatic systems (Detenbeck et al 1996;Graymore et al 2001).…”
Section: Efficacy Of the Bioremediation Tool In Soil Retention Functisupporting
confidence: 73%
“…In contrast, an increase in chlorophyll c relative to chlorophyll a at 12 μg/L atrazine was observed in an earlier periphytometer experiment, suggesting that chlorophyll c containing Bacillariophyceae were more atrazine tolerant compared to the Chlorophyceae (Kish, 2006). Detenbeck et al (1996) observed reductions in gross primary productivity at 15 μg/L atrazine but a similar reduction was not observed at higher concentrations. However, they also provided evidence of a shift in species dominance or selection for tolerant species at ≥50 μg/L atrazine.…”
Section: Experimental Effects Of Nutrients and Atrazine On Periphytonmentioning
confidence: 65%
“…However, an explanation for this effect is hard to find. Overcompensation of slight impairment in photosynthetic activity would be analogous to the response under light limitation (Kemp et al 1985;Detenbeck et al 1996). Decreased competition for nutrients due to direct and more severe effects on phytoplankton could be another possibility.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the second application led to higher TBA concentrations but not to a more pronounced effect on functional parameters or phytoplankton abundance. Other studies have demonstrated that tolerant species may replace herbicide-affected species in the phytoplankton or periphyton (Detenbeck et al 1996;Cuppen et al 1997;Hartgers et al 1998). Explaining the lack of effect on algal abundance after the second TBA application with development of TBA resistant chryptophyceen strains or other algae within only 4 weeks would be highly hypothetical and needs confirmation.…”
Section: Discussionmentioning
confidence: 99%